2018
DOI: 10.4018/ijtd.2018040103
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intention to Use Local E-Government Services in Ghana

Abstract: The purpose of this article is to investigate factors determining the intention to adopt and use local e-government services in Ghana. A research questionnaire was administered to potential respondents in Municipal, Metropolitan and District Assemblies (MMDAs). The data was analyzed with SPSS while the Technology Acceptance Model (TAM) was used as the theoretical framework for this study. The results demonstrated that, apart from education, demographic factors such as age and gender were all significant and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…It is however imperative to contextualize technology acceptance and use in other to develop frameworks that suit specific cultural settings or design limitations (Rahayu and Day, 2015). Again, research into technology acceptance has also focused predominantly on ICT usage within the educational sector (Kolog et al, 2015), mobile banking and financial technologies (Boateng et al, 2016), e-government and e-governance (Mensah and Mi, 2018) with less attention on shipping activities. Thus, there is less empirical evidence and literature on factors that impacts technology acceptance within the shipping industry, and the situation is unacceptably scary when considering shipping industries in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…It is however imperative to contextualize technology acceptance and use in other to develop frameworks that suit specific cultural settings or design limitations (Rahayu and Day, 2015). Again, research into technology acceptance has also focused predominantly on ICT usage within the educational sector (Kolog et al, 2015), mobile banking and financial technologies (Boateng et al, 2016), e-government and e-governance (Mensah and Mi, 2018) with less attention on shipping activities. Thus, there is less empirical evidence and literature on factors that impacts technology acceptance within the shipping industry, and the situation is unacceptably scary when considering shipping industries in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Its proposed model provides a different approach as its main focus is on examining the direct impact of demographic factors (specifically, age, education, and income) on the adoption of one e-government service and application, that is, e-voting. In Ghana, a developing country in Africa, Mensah and Mi's (2018b) study confirmed the direct impact of education, age, and gender on e-government services' adoption. Kose (2019) conducted a study in Turkey and found that household income, education level, and frequency of internet use were positively correlated with the probability of e-government use by Turkish citizens.…”
Section: E-voting Adoption and The Digital Dividementioning
confidence: 67%
“…(19) Citizens mentioned lack of promotion and exposure as the key factors for their lack of awareness in response to low-usage consumers. (20) It was found that a citizen's attitude is the most crucial factor influencing whether or not they will accept and use e-government services [101]. (21) According to the findings, citizens' degree of satisfaction has a substantial influence on their intention to utilise e-government services.…”
Section: Resultsmentioning
confidence: 99%